2009
DOI: 10.1002/chir.20725
|View full text |Cite
|
Sign up to set email alerts
|

Integration of metabolomics and in vitro metabolism assays for investigating the stereoselective transformation of triadimefon in rainbow trout

Abstract: Triadimefon is a systemic agricultural fungicide of the triazole class whose major metabolite, triadimenol, also a commercial fungicide, provides the majority of the actual fungicidal activity, i.e., inhibition of steroid demethylation. Both chemicals are chiral: triadimefon has one chiral center with two enantiomers while its enzymatic reduction to triadimenol produces a second chiral center and two diastereomers with two enantiomers each. All six stereoisomers of the two fungicides were separated from each o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 25 publications
2
32
1
Order By: Relevance
“…The EF measured for each of the four triadimenol stereoisomers are calculated according to Eq. (2) (Kenneke et al, 2010).…”
Section: Ef ¼ Concentration Of ðàþ ðàþþðþþ ð1þmentioning
confidence: 99%
See 1 more Smart Citation
“…The EF measured for each of the four triadimenol stereoisomers are calculated according to Eq. (2) (Kenneke et al, 2010).…”
Section: Ef ¼ Concentration Of ðàþ ðàþþðþþ ð1þmentioning
confidence: 99%
“…The stereoselective formation of TF and TN is an important issue in ecological risk assessment when considering the difference in fungicidal activity and toxicity among the enantiomers (Li et al, 2014). Stereoselective metabolism of TF to TN has been observed in soil microorganisms and rainbow trout (Garrison et al, 2011;Kenneke et al, 2010;Li et al, 2011). Unfortunately, the stereoselectivity of TF and TN in reptiles have never been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [9,10] developed a method for simultaneous separation of TF and TN by sulfated b-cyclodextrin-mediated CE, and applied this method to study biotransformation of TF to TN by soil microorganisms. Kenneke et al [5] reported on the integration of metabolomics and in vitro metabolism assays for investigating the stereoselective transformation of TF in rainbow trout by GC-MS. Dong et al [24] analyzed stereoselective degradation of TN in cucumber plants by HPLC. Compared with CE and HPLC, the extraction and purification procedures of this LC-MS/MS method were fast and the sensitivity was better.…”
Section: Comparison With Previous Methodsmentioning
confidence: 99%
“…TF was a systemic fungicide that acts by inhibiting steroid demethylation, and used to control powdery mildews and fungi on fruits, vegetables, wheat, and other agricultural crops. It has a single chiral center and correspondingly present two enantiomers, and can be enzymatically reduced to TN with four stereoisomers in plants, soil, and fungi [5]. The (1S, 2R)-isomer has the highest fungicidal activity (up to 1000-fold more active than the other three) in four stereoisomers of TN [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation